EFEKTIVITAS MENTORING TERHADAP PENGAMALAN KEAGAMAAN MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SRIWIJAYA PALEMBANG - Nurlaila Nurlaila; Enok Rohayati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
The purposes of the study are to describe the implementation of mentoring program and religious practice, and to find out the effectiveness of the mentoring program on student religious practice. This is a mixed qualitative quantitative research. The results show that Islamic Education mentoring activities in increasing religious practice had achieved overall success, amounting to 90%. The mentoring program can achieve the objectives planned previously. The effectiveness of the mentoring program is indicated by a tcount of 7.343> 1.70 t table, with the level of significance 0.00 <0.05. From the results of the descriptive analysis, it was found that the percentage of mentoring activities was 75% and the percentage of religious practice was 83%.. It can be summarized that Mentoring activities of Islamic Religion are effectively carried out to foster student religious practice at Teaching and Education Faculty of Sriwijaya University Palembang.